2015
DOI: 10.1037/xge0000040
|View full text |Cite
|
Sign up to set email alerts
|

Affective processing requires awareness.

Abstract: Studies using backward masked emotional stimuli suggest that affective processing may occur outside visual awareness and imply primacy of affective over semantic processing, yet these experiments have not strictly controlled for the participants' awareness of the stimuli. Here we directly compared the primacy of affective versus semantic categorization of biologically relevant stimuli in 5 experiments (n = 178) using explicit (semantic and affective discrimination; Experiments 1-3) and implicit (semantic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 129 publications
13
101
1
Order By: Relevance
“…According to post-attentional models of emotional processing, perceptual analysis is performed and the features of objects must be integrated, and possibly the objects themselves must be identified, prior to affective processing (Cave & Batty, 2006;Lähteenmäki, Hyönä, Koivisto, & Nummenmaa, 2015;Nummenmaa, Hyönä, & Calvo, 2010;Storbeck, Robinson, & McCourt, 2006). In line with this view, perceptual priming has been found to occur earlier (<170 ms) than affective priming (between 340 and 550 ms) in the discrimination of facial expressions (Calvo et al, 2012).…”
Section: Perceptual Processing Drives Expression Recognitionmentioning
confidence: 77%
“…According to post-attentional models of emotional processing, perceptual analysis is performed and the features of objects must be integrated, and possibly the objects themselves must be identified, prior to affective processing (Cave & Batty, 2006;Lähteenmäki, Hyönä, Koivisto, & Nummenmaa, 2015;Nummenmaa, Hyönä, & Calvo, 2010;Storbeck, Robinson, & McCourt, 2006). In line with this view, perceptual priming has been found to occur earlier (<170 ms) than affective priming (between 340 and 550 ms) in the discrimination of facial expressions (Calvo et al, 2012).…”
Section: Perceptual Processing Drives Expression Recognitionmentioning
confidence: 77%
“…This chosen latency also resulted in an adequate at-chance stimuli recognition level, as tested at the end of the study. Yet, a recent study (Lähteenmäki et al, 2015) suggested that partial awareness could be present after display durations of 40 ms. Whether completely non-conscious activation was achieved or some awareness was present, only face stimuli induced a significant subliminal effect, suggesting that the chosen 33 ms presentation was effective in differentiating between Stimulus types.…”
Section: Discussionmentioning
confidence: 99%
“…When tightly controlled CS exposure conditions and sensitive awareness checks are used, meeting methodological requirements currently advised in cognitive psychological research (Atas, Vermeiren, & Cleeremans, 2013;Pratte & Rouder, 2009;Shanks & St. John, 1994), objective identification appears to be a necessary yet insufficient condition for an EC effect to emerge . As to subliminally presented affective stimuli (i.e., USs), they have recently been shown to elicit no affective response (Lähteenmäki, Hyönä, Koivisto, & Nummenmaa, 2015).…”
Section: Discussionmentioning
confidence: 99%